2018
DOI: 10.1167/iovs.18-25517
|View full text |Cite
|
Sign up to set email alerts
|

Association of Upregulated Angiogenic Cytokines With Choroidal Abnormalities in Chronic Central Serous Chorioretinopathy

Abstract: PURPOSE. To clarify the distinct molecular pathogenesis of central serous chorioretinopathy (CSC) and pachychoroid neovasculopathy (PNV). METHODS. Aqueous humor (AH) was collected from 18 acute CSC, 20 chronic CSC, and 20 PNV patients. Concentrations of 30 cytokines in the AH were analyzed using a multiplex bead immunoassay, and the cytokine profiles were compared among these three groups of patients. The areas of choroidal vascular hyperpermeability (CVH) and choroidal thickness (CT), including measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Intraocular concentrations of IL-6 and IL-8 have been reported to be closely associated with the volume of MO and size of active CNV 175 , 182 . Moreover, IL-6 and IL-8 are significantly upregulated in the chronic CSC group compared with the acute CSC or PNV groups 272 . Therefore, further studies are needed to elucidate the role of IL-6 in the aetiology of AMD, CNV and pachychoroid spectrum diseases.…”
Section: Discussionmentioning
confidence: 90%
“…Intraocular concentrations of IL-6 and IL-8 have been reported to be closely associated with the volume of MO and size of active CNV 175 , 182 . Moreover, IL-6 and IL-8 are significantly upregulated in the chronic CSC group compared with the acute CSC or PNV groups 272 . Therefore, further studies are needed to elucidate the role of IL-6 in the aetiology of AMD, CNV and pachychoroid spectrum diseases.…”
Section: Discussionmentioning
confidence: 90%
“…22,31 Also, elevation of complement activation products (complement factors Ba, H, I, C3a, 25,26 adhesion molecule-1, IL-6, IL-8, IP-10, C-reactive protein, angiopoietin-2, human growth factor, tissue inhibitor of metalloproteinases 1, C-X-C motif chemokines 12 and 13, tumor necrosis factor-α, IL-31, leukemia inhibitory factor, and stromal cell-derived factor-1-α. [7][8][9][10][11][12][13][14][15][16][32][33][34][35][36] A recent study that summarized these cytokine networks using cluster analysis suggested that VEGF and MCP-1 were key factors in the development of nAMD. 15 Although complement factors and angiogenic cytokines were associated with nAMD development, their relationships in the aqueous humor have not been fully determined.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term treatment results of this study suggest that IVBIs can remain as a treatment option for patients with CSC. Previously, some studies have investigated the cytokines in the aqueous humor of patients with CSC, resulting in inconsistent results [40][41][42][43]. Some studies suggest that aqueous VEGF level was not significantly elevated in the patients with CSC, supporting ineffectiveness of anti-VEGF therapy in these patients [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that the VEGF-A level is significantly higher in bevacizumab responders than in non-responders, suggesting that VEGF may contribute to the pathogenesis of CSC [42]. Another study found that proinflammatory cytokines, such as interleukin (IL)-6 and IL-8, are significantly upregulated in patients with chronic CSC compared to those with acute CSC [43]. Angiogenic cytokines and VEGF-A are also upregulated more in patients with CSC than in those with acute CSC [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation